Emprego de um polímero de impressão molecular restrito à ligação com macromoléculas por meio de revestimento com albumina para extração on-line de ivermectina em carne bovina seguido de análise por HPLC-UV - Lima, Marcela Marília De (2014)
Ivermectn (IVM) is an antiparasitic drug worldwide used in livestock. However, when the grace period is not respected, IVM residues can be found in animal source products and can cause damages to the human health. Thus, it was established in many countries a maximum limit of residue (MRL) to this drug. Therefore, meat samples that contain IVM above the established values are considered adulterated and have been the cause of exportations embargo of meat from Brazil. IVM is able to produce a therapeutic effect even in lower doses. Hence, the residues levels in the tissues are usually very low, which makes necessary the use of selective and sensitive techniques of sample preparation and analysis. Thus, the main objective of this work was to synthesize a restricted access molecularly imprinted polymer coated with bovine serum albumin (RAMIP-BSA) and to employ it in the on-line extraction of IVM in minced meat samples, followed by a high performance liquid chromatography (HPLC) with an UV detector. The method has shown linearity from 50 to 500 μg kg-1, with precision and accuracy ranging from 3.8 to 17.0 and from -18.5 to 22.0, respectively. The detection and quantification limits were 30 e 50 μg kg-1 respectively. The method can be used in the monitoring of IVM in beef samples.